Worldly goods : a new history of the Renaissance - Jardine, Lisa (New York ; London : W. W. Norton, 1996)
"Fascinating . . . Jardine's attention to the material side of things is an important explanatory complement to the many histories of the period that have dwelt on the sublime works of art . . . Real history is in the details, the small stories, of which WORLDLY GOODS is a treasure house."
Richard Bernstein, The New York Times
Str. 437-452: Bibliografija
Kazalo
Keywords: renesansa; gospodarska povijest -- 15. st. -- 16. st